Distribution of influenza virus types by age using case-based global surveillance data from twenty-nine countries, 1999-2014 - Saverio Caini; Peter Spreeuwenberg; Gabriela F. Kusznierz; Juan Manuel Rudi; Rhonda Owen; Kate Pennington; Sonam Wangchuk; Sonam Gyeltshen; Walquiria Aparecida Ferreira de Almeida; Cláudio Maierovitch Pessanha Henriques; Richard Njouom; Marie-Astrid Vernet; et al. (BMC Infectious Diseases, 2018)
Abstract Background Influenza disease burden varies by age and this has important public health implications. We compared the proportional distribution of different influenza virus types within age strata using surveillance data from twenty-nine countries during 1999-2014 (N=358,796 influenza cases). Methods For each virus, we calculated a Relative Illness Ratio (defined as the ratio of the percentage of cases in an age group to the percentage of the country population in the same age group) for young children (0-4 years), older children (5-17 years), young adults (18-39 years), older adults (40-64 years), and the elderly (65+ years). We used random-effects meta-analysis models to obtain summary relative illness ratios (sRIRs), and conducted meta-regression and sub-group analyses to explore causes of between-estimates heterogeneity. Results The influenza virus with highest sRIR was A(H1N1) for young children, B for older children, A(H1N1)pdm2009 for adults, and (A(H3N2) for the elderly. As expected, considering the diverse nature of the national surveillance datasets included in our analysis, between-estimates heterogeneity was high (I2>90%) for most sRIRs. The variations of countries’ geographic, demographic and economic characteristics and the proportion of outpatients among reported influenza cases explained only part of the heterogeneity, suggesting that multiple factors were at play. Conclusions These results highlight the importance of presenting burden of disease estimates by age group and virus (sub)type.